Corrosion Behaviour of Stainless Steel 316L in Chloride Environment After Dry Machining by Face Milling at Various Spindle Speed - Widodo, Teguh; Raharjo, Rudianto; Bintarto, Redi; Alamsyah, Fikrul Akbar; Wahyudiono, Arif; Choiron, Moch Agus (International Journal of Integrated Engineering, 2024)
This study attempts to investigate the impact of spindle speed on the corrosion characteristics of 316L stainless steel during the face milling process in dry condition. The machining parameters, such as spindle speed, have an impact on the surface properties of the material after the processes. It is essential to devote significant attention that these parameters can still affect the surface condition of 316L stainless steel, which may then affect its corrosion properties. This research aimed to examine the corrosion characteristics of 316L stainless steel subsequent to the face milling process using the potentiodynamic polarization technique in a chloride-containing environment. The face milling technique use a 6 mm carbide cutter tool, with spindle speed variations of 1800 rpm, 1600 rpm, and 1400 rpm. The feed rate is maintained in constant rate, which is 0.002 mm/rev. The findings of the corrosion rate test indicate that variations in spindle speed lead to fluctuations in the corrosion rate value. There finding shows an inverse relationship between the value of spindle speed and the corrosion rate, wherein an increase in spindle speed corresponds to a decrease in the corrosion rate